TINJAUAN FITOREMEDIASI LIMBAH BATIK PEKALONGAN MENGGUNAKAN AGEN ECENG GONDOK (Eichornia crassipes) SEBAGAI IMPLEMENTASI Q. S. AL-BAQARAH AYAT 30 - Khusna, Khotimatul; Fatimah, Siti (Kaunia: Integration and Interconnection Islam and Science Journal, 2023)
Community interest in batik art has increased from time to time, in line with the increase in batik production in Pekalongan. It will impact the waste produced as well. The batik waste without processing causes pollution and environmental damage. Phytoremediation actions can be used as a form of solution to manage the waste pollution. The purpose of this article is to examine the practice of Q. S. Al-Baqarah verse 30 in batik waste by phytoremediation using Water hyacinth (Eichornia crassipes). This article used literature review and self-observation methods to construct the data based on evidence. The review covers 25 journal articles published after 2010 in Bahasa from Goggle Scholar, Research Gate, and Google Books. Based on the results, the phytoremediation of Pekalongan batik waste using water hyacinth can be applied. This is a way of implementing the human mandate as caliph on earth in protecting the environment.